Utility of paired blood cultures and smears in diagnosis of disseminated Mycobacterium avium complex infections in AIDS patients. - Stone, B L (1994)
For 273 patients evaluated for disseminated Mycobacterium avium complex infection, a total of 1,047 mycobacterial blood cultures (MBCs) were submitted; the M. avium complex was recovered from 140 (13%) of the specimens. Results for the paired MBCs were highly concordant: in 392 of 462 (85%) culture sets, both MBCs were negative, in 53 of 462 (11%) sets, both MBCs were positive, and in only 17 of 462 (4%) sets was one culture positive and the other negative. Acid-fast smears were done on sediments from 671 specimens; smears were positive for 4 of 98 (4%) cultures that grew the M. avium complex. A single MBC should be obtained and then repeated if negative and disseminated M. avium complex infection is still clinically suspected. Use of direct acid-fast smears of sediments is not a reliable means of detecting mycobacteremia.